Designing A Keyboard Learning Model for Worship Musician Regeneration: A Study at GKSBS Daya Murni Lampung - Saputra, Daniel Adi; Nainggolan, Oriana Tio Prahita; Samosir, Tanesya Hotris (Pusat Penelitian dan Pengabdian Masyarakat STAKPN Sentani, 2025)
The shortage of skilled worship accompanists in Indonesian churches, including GKSBS Daya Murni in Lampung, underscores the need for structured and contextual training. This study designed and implemented a phased keyboard learning model to regenerate younger congregants as competent accompanists. Using a qualitative descriptive approach, three teenage participants were purposively selected, and data were gathered through observation, interviews, and documentation. The findings show steady progress from basic posture and scales to chord application, transposition, and worship accompaniment. Instruction embedded in real services enhanced confidence, liturgical awareness, and readiness to serve. The study’s novelty lies in integrating structured pedagogy, worship context, and mentoring as a sustainable regeneration framework for small churches facing accompanist shortages.